Spectrofluorimetric method for atenolol determination based on gold nanoparticles - Bakir Esam; Gouda Mohamed; Alnajjar Ahmed; Boraie Waleed E. (Acta Pharmaceutica)
A simple and sensitive spectrofluorimetric method for determination of atenolol (ATE) using gold nanoparticles (AuNPs) was developed. The method is based on the quenching effect of atenolol on photoluminescence of AuNPs at λem = 705 nm. Variables affecting luminescence of gold nanoparticles such as the solvent, pH value and surfactant were studied and optimized. The method was preliminarily validated according to ICH guidelines. A linear correlation was recorded within the range of 1.0–10 mg mL−1 ATE with the coefficient of determination R2 of 0.999. The limit of detection and limit of quantitation for atenolol were found to be 0.87 and 2.64 mg mL−1, resp. Good recoveries in the range of 98.7–100.0 % were obtained for spiked samples. The proposed method was applied successfully to assaying atenolol in pharmaceuticals formulations.